KARAKTERISTIK TAFSIR AL-MARĀGHĪ DAN PENAFSIRANNYA TENTANG AKAL - M. Khoirul Hadi (Hunafa: Jurnal Studia Islamika, 2014)
This article discusses the methodology of al-Marāghī interpretation, especially in a study about the ratio. Tafsir al-Marāghī has unique characteristics. This interpretation in the reviewer's favorite by using the adab al-ijtimā’ī method of interpretation, brief writing style, as well as terms that are easy to understand. Al-Marāghī intentionally omit discussion of non-essential, such as nahw-ṣarf aspects, so that the reader does not get stuck on the text but the context of interpretation. In the problem of ratio, al-Marāghī have a better opinion of the group of theologians developed in the community, according to al-Marāghī sense capable of distinguishing between God's promise to the promise of Satan, reason can also believes in the afterlife after this life, this second opinion is not appears on the opinion of theologians before al-Marāghī.Kata Kunci: al-Marāghī, sistematik, adab al-Ijtimā’ī. -SA;t :@:/span>dakwah, komunikasi, perspektif Alquran ansifga:@:mso-fareast-language:EN-US;mso-bidi-language:AR-SA'>:        Corak, quasi-Obyektifis Tradisionalis, Obyektifis, quasi Obyektifis Modernis